2018
DOI: 10.1016/j.commatsci.2018.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the thermodynamic stability of perovskite oxides using machine learning models

Abstract: Perovskite materials have become ubiquitous in many technologically relevant applications, ranging from catalysts in solid oxide fuel cells to light absorbing layers in solar photovoltaics. The thermodynamic phase stability is a key parameter that broadly governs whether the material is expected to be synthesizable, and whether it may degrade under certain operating conditions. Phase stability can be calculated using Density Functional Theory (DFT), but the significant computational cost makes such calculation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(141 citation statements)
references
References 41 publications
1
132
0
1
Order By: Relevance
“…Schmidt et al used high‐throughput DFT to calculate 249 984 potential cubic ABX 3 perovskites and found that ML can reproduce the energetics data with errors just over 100 meV per atom . Li et al trained an ML model based on the thermodynamics data of 1929 oxide perovskites from the Materials Project and intended to predict more oxide perovskites beyond the training set . Xie and Grossman established a smart crystal graph of convolutional neural networks based on DFT‐calculated data in the Materials Project to predict materials properties directly from crystal structures; based on their model, 228 perovskites were deemed potentially synthesisable …”
Section: Resultsmentioning
confidence: 99%
“…Schmidt et al used high‐throughput DFT to calculate 249 984 potential cubic ABX 3 perovskites and found that ML can reproduce the energetics data with errors just over 100 meV per atom . Li et al trained an ML model based on the thermodynamics data of 1929 oxide perovskites from the Materials Project and intended to predict more oxide perovskites beyond the training set . Xie and Grossman established a smart crystal graph of convolutional neural networks based on DFT‐calculated data in the Materials Project to predict materials properties directly from crystal structures; based on their model, 228 perovskites were deemed potentially synthesisable …”
Section: Resultsmentioning
confidence: 99%
“…Generally, the stability of materials can be evaluated by the energy above the convex hull ( E hull ). Li et al established a ML model to predict E hull of perovskite oxides learning from over 1900 DFT computed perovskite oxides. Then the model was used to predict 15 novel perovskite compounds.…”
Section: Achievements Of ML In Energy Storage and Conversion Materialsmentioning
confidence: 99%
“…We leveraged the internally and externally enriched databases for hydrogen production as a baseline to train, improve, and optimize AI‐driven learning algorithms for discovery of electrocatalysts . Intercorrelation models already developed for water splitting electrocatalysts are extensively utilized as well …”
Section: Virtual Materials Intelligence Platformmentioning
confidence: 99%